Strategi Fundraising Badan Amil Zakat Nasional Kabupaten Jepara dalam Meningkatkan Penerimaan Dana Zakat (Institut Agama Islam Negeri Kudus, 2024)
AbstractFundraising affects the rise and fall of a zakat management institution. Therefore, an implementation strategy is needed in its implementation. In this case, BAZNAS Jepara Regency is one of the zakat management institutions implementing fundraising strategies in zakat fund collection activities. A fundraising strategy is the starting point for identifying an organization's needs so that its operations can be improved to meet increasing demand. The fundraising strategy determines the success or failure of an organization or institution in raising funds for the present and the future. Fundraising plays a key role for social institutions or organizations when they want to implement programs within the framework of planned activities. This research aims to find out what fundraising strategies are used by BAZNAS Jepara Regency to increase the receipt of zakat funds. This research is field research with a qualitative approach. Data collection techniques through observation, interviews, and documentation. The data validity test in this research is triangulation, namely source triagulation and time triagulation. Data analysis techniques include data reduction, data presentation, and conclusions. The results of this research show that the existing zakat fund fundraising strategy at BAZNAS Jepara Regency is based on existing theory. This can be seen from the formulation of the fundraising strategy and the implementation of the fundraising strategy that has been used. The formulation of the BAZNAS fundraising strategy that has been used to attract muzakki's interest in distributing their zakat is by the RKAT that has been created. The implementation of the fundraising strategy that has been carried out by BAZNAS Jepara Regency is by searching for muzakki data, outreach with the general public and ASN, picking up football, banking channels, and online fundraising.Keywords: Fundraising Strategy; Zakat; BAZNAS. AbstrakFundraising mempunyai dampak terhadap naik turunnya suatu lembaga pengelolaan zakat. Oleh karena itu, diperlukan strategi implementasi dalam pelaksaannya. Dalam hal ini BAZNAS Kabupaten Jepara yang merupakan salah satu lembaga pengelola zakat yang menerapkan strategi fundraising dalam kegiatan penghimpunan dana zakat. Strategi fundraising adalah titik awal untuk mengidentifikasi kebutuhan organisasi sehingga operasinya dapat ditingkatkan untuk memenuhi permintaan yang kian meningkat. Strategi fundraising sangat menentukan berhasil atau tidaknya suatu organisasi atau lembaga dalam menghimpun dana untuk masa kini dan yang akan datang. Fundraising memegang peranan penting bagi lembaga atau organisasi sosial ketika ingin melaksanakan program dalam rangka kegiatan yang direncanakan. Tujuan penelitian ini adalah mengetahui bagaimana strategi fundraising yang digunakan BAZNAS Kabupaten Jepara dalam meningkatkan penerimaan dana zakat. Penelitian ini merupakan penelitian lapangan dengan pendekatan kualitatif. Teknik pengumpulan data melalui kegiatan observasi, wawancara, dan dokumentasi. Uji keabsahan data dalam penelitian ini adalah triagulasi yakni triagulasi sumber dan triagulasi waktu. Teknik analisis data berupa reduksi data, penyajian data, dan kesimpulan. Hasil penelitian ini menunjukkan bahwa strategi fundraising dana zakat di BAZNAS Kabupaten Jepara yang ada telah sesuai dengan teori yang ada. Hal ini dapat dilihat dari formulasi strategi fundraising dan implementasi strategi fundraising yang telah digunakan. Formulasi strategi fundraising BAZNAS yang telah digunakan dalam menarik minat muzakki dalam menyalurkan zakatnya telah sesuai dengan RKAT yang telah dibuat. Implementasi strategi fundraising yang telah dilakukan BAZNAS Kabupaten Jepara adalah dengan melakukan pencarian data para muzakki, sosialisasi dengan masyarakat umum dan ASN, jemput bola, banking channel, dan online fundraising. Kata Kunci: Strategi Fundraising; Zakat; BAZNAS.